2014
DOI: 10.1021/jf502180j
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effect of a Wild Blueberry Anthocyanin-Rich Extract in Human Caco-2 Intestinal Cells

Abstract: Intestinal inflammation is a natural process crucial for the maintenance of gut functioning. However, abnormal or prolonged inflammatory responses may lead to the onset of chronic degenerative diseases, typically treated by means of pharmacological interventions. Dietary strategies for the prevention of inflammation are a safer alternative to pharmacotherapy. Anthocyanins and other polyphenols have been documented to display anti-inflammatory activity. In the present study, three bioactive fractions (anthocyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 50 publications
6
52
1
Order By: Relevance
“…The present data are in accordance with other previous studies reporting the inhibitory activity of anthocyanins on the NF- κ B proinflammatory pathway in Caco-2 cells [10, 31, 32]. Furthermore, in vivo studies demonstrated that feeding pigs with an anthocyanin-rich extract reduces transactivation of NF- κ B in the duodenal mucosa and in turn lowers transcript levels of various NF- κ B target genes involved in the inflammatory process [33].…”
Section: Discussionsupporting
confidence: 93%
“…The present data are in accordance with other previous studies reporting the inhibitory activity of anthocyanins on the NF- κ B proinflammatory pathway in Caco-2 cells [10, 31, 32]. Furthermore, in vivo studies demonstrated that feeding pigs with an anthocyanin-rich extract reduces transactivation of NF- κ B in the duodenal mucosa and in turn lowers transcript levels of various NF- κ B target genes involved in the inflammatory process [33].…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies show that Blueberries ( Vaccinium sp .) may beneficially modulate the immunological profile distinct from inhibiting pro-inflammatory molecules [1822]. In the present study the free radical scavenging ability of blueberries was evaluated by the quantitative analysis of free radicals, neurotransmitters, protein and gene expression of inflammatory cytokines in a PTSD inducing rat model.…”
Section: Introductionmentioning
confidence: 99%
“…Blueberry fruits have been the focus of much recent attention due to numerous reports of their positive effects on human health. These benefits are generally attributed to high levels of flavonoids, AsA, and mineral composition (Prior, Lazarus, Cao, Muccitelli, & Hammerstone, 2001;Rasmussen, Frederiksen, Struntze Krogholm, & Poulsen, 2005;Tan et al, 2014;Taverniti et al, 2014). However, compared with the considerable research focused on the flavonoid metabolism of blueberries, little information is currently available on the mechanism controlling AsA levels in blueberries to date.…”
Section: Introductionmentioning
confidence: 99%